计算:(1)8+(-6)+5+(-7)(2)−33÷34×(-查字典问答网
分类选择

来自姜小光的问题

  计算:(1)8+(-6)+5+(-7)(2)−33÷34×(−23)2−(−1)7(3)(−56+38−112)×(−24)(4)−6÷(−43)−(1−0.2÷15)×(−2)(5)−14÷(−2)3×(−135)+|0.8−1|.

  计算:

  (1)8+(-6)+5+(-7)

  (2)−33÷34×(−23)2−(−1)7

  (3)(−56+38−112)×(−24)

  (4)−6÷(−43)−(1−0.2÷15)×(−2)

  (5)−14÷(−2)3×(−135)+|0.8−1|.

1回答
2020-09-0711:48
我要回答
提示:回答问题需要登录哦!
侯山峰

  (1)原式=8-6+5-7=2-2=0;(2)原式=-27×43×49-(-1)=-16+1=-15;(3)原式=-56×(-24)+38×(-24)-112×(-24)=20-9+2=11+2=13;(4)原式=-6×(-34)-(1-15×5)×(-2)=92-0=92;(5)原式=-1×(-18...

2020-09-07 11:52:55
大家都在问
最新问答